Peran Media Daring pada Konflik Sumber Daya Alam di Riau - M Rawa El Amady (Jurnal ILMU KOMUNIKASI, 2022)
This article discusses the role of online media in natural resource conflicts in Riau during 2016-2018. The conflict has always been at national highest position, even though there are 323 online media that should be able to accelerate conflict resolution. The research is conducted using qualitative content analysis with data from the annual report on conflict news in 2016-2018, and analyzed based on news content and media trends. The findings show that online media plays a function of conflict diminisher for economic interests. In the process, there are parties involved, namely investors, local communities, media, and the government.